An energy-based approach for kinetostatic modeling of general compliant mechanisms. (December 2019) - Wu, Shilei; Shao, Zhongxi; Su, Haijun; Fu, Hongya
Highlights: An energy-based kinetostatic modeling approach for general compliant mechanisms is presented. The laborsome equilibrium equations of nodal force are avoided to solve. The screw theory is combined with the energy method for kinetostatic modeling of general compliant mechanisms. Abstract: Kinetostatic analysis for general compliant mechanisms requires simultaneous considerations of kinematic and elasto-mechanical behaviors. Therefore, it will be difficult and low-efficiency to design and analyze general compliant mechanisms. In this paper, a kinetostatic modeling approach that integrates the screw theory with the energy method is proposed to provide an accurate and efficient solution. The coordinate transformations of stiffness and compliance matrices are deduced by using the screw theory. Then, the kinetostatic modeling of general compliant mechanisms is presented based on the energy method and the screw theory. The advantage of the proposed modeling approach is that there is no need to solve the laborsome equilibrium equations of nodal force when it is applied to the kinetostatic analysis of general compliant mechanisms. Performance comparisons of the proposed approach with the matrix displacement approach and the finite element analysis are respectively conducted for three exemplary mechanisms to reveal the prediction accuracy. The results indicate that the proposed modeling approach is applicable for fast performance evaluation of general compliant mechanisms at the early design stage.